Characteristics of firms that issue redeemable convertible preferred stock: Evidence from South Korea - Geum-Ok Sim; Hyun-Ah Lee (Global Business & Finance Review (GBFR), 2022)
Purpose: The issuance of redeemable convertible preferred stock (RCPS) has been steadily increasing in Korea since the revision of the Commercial Act, which allows firms to issue various types of stocks, in 2010. This study aims to verify equity financing behavior by examining the characteristics of firms that issue RCPS. Design/methodology/approach: Using a sample of 12,768 firm-year observations of Korean listed companies from 2011 to 2018, this study conducts univariate and multivariate analyses to examine the factors that affect firms' decisions regarding RCPS issuance. For multivariate analysis, logistic regression analysis is used. Findings: This study shows that firms issuing RCPS have higher debt ratios and lower operating cash flows than non-issuing firms. It is also found that firms issuing RCPS are smaller and younger than non-issuing firms. These findings indicate that firms with higher costs of financial distress, lower internal cash flow, and lower credibility/reputation are more likely to issue RCPS because they are constrained by debt capacity. Research limitations/implications: According to pecking order theory, firms prefer debt over equity if external funds are required. The results of this study support the pecking order theory by providing evidence that firms rely on hybrid securities financing like redeemable preferred stock, a priority after debt when they are constrained by debt capacity. Originality/value: This study sheds light on financing decisions related to the issuance of hybrid securities from the perspective of pecking order theory. It also contributes to broadening the scope of research on hybrid securities by providing empirical evidence on the financial characteristics of firms that issue RCPS.
Keywords: 650; Capital Structure; Debt; Equity; Hybrid Securities; Redeemable Convertible Preferred Stock